First update of the International Xenotransplantation Association consensus statement on conditions for undertaking clinical trials of porcine islet products in type 1 diabetes—Chapter 2a: source pigs—preventing xenozoonoses. (4th March 2016) - Spizzo, Thomas; Denner, Joachim; Gazda, Lawrence; Martin, Michael; Nathu, Divya; Scobie, Linda; Takeuchi, Yasuhiro
Abstract: Chapter 2 of the original consensus statement published in 2009 by IXA represents an excellent basis for the production of safe donor pigs and pig‐derived materials for porcine islet xenotransplantation. It was intended that the consensus statement was to be reviewed at interval to remain relevant. Indeed, many of the original salient points remain relevant today, especially when porcine islet xenotransplantation is performed in conjunction with immunosuppressants. However, progress in the field including demonstrated safe clinical porcine xenograft studies, increased understanding of risks including those posed by PERV, and advancement of diagnostic capabilities now allow for further consideration. Agents of known and unknown pathogenic significance continue to be identified and should be considered on a geographic, risk‐based, dynamic, and product‐specific basis, where appropriate using validated, advanced diagnostic techniques. PERV risk can be sufficiently reduced via multicomponent profiling including subtype expression levels in combination with infectivity assays. Barrier facilities built and operated against the AAALAC Ag Guide or suitable alternative criteria should be considered for source animal production as long as cGMPs and SOPs are followed. Bovine material‐free feed for source animals should be considered appropriate instead of mammalian free materials to sufficiently reduce TSE risks. Finally, the sponsor retention period for archival samples of donor materials was deemed sufficient until the death of the recipient if conclusively determined to be of unrelated and non‐infectious cause or for a reasonable period, that is, five to 10 yrs. In summary, the safe and economical production of suitable pigs and porcine islet xenograft materials, under appropriate guidance and regulatory control, is believed to be a viable means of addressing the unmet need for clinical islet replacement materials.